Legal Reform In the Enforcement of Juvenile Criminal Law - Anwar*, Aulia Citra; Fadly, Ovan Setiawan; Bustani, Simona (Riwayat: Educational Journal of History and Humanities, 2023)
The presence of negotiations in crimes involving children aged 12-18 years and legal gaps in crimes involving children under 12 years, as well as the continued occurrence of repeated offenses, indicate that law enforcement against juvenile crimes has not been running optimally. The community seems resigned to the legal system, leaving them no choice but to follow the existing Legal Culture. By employing a juridical-normative approach and descriptive-analytical methods, this research aims to provide an overview of legal culture in the enforcement of juvenile criminal law. The research findings indicate that the Legal Culture is still very low, suggesting the need for legal reform, such as creating regulations regarding repeated offenses in crimes involving children under 12 years, establishing a Child Police and a Children's Court, and utilizing social research through the Children's Court as a stepping stone to improve Legal Culture.